Pharmacokinetic Comparison of Oral Bacampicillin and Parenteral Ampicillin - Bergan, Tom (1978)
Bacampicillin is a new oral prodrug which is rapidly converted to ampicillin during absorption from the gastrointestinal tract. High serum peaks of ampicillin are obtained. Bacampicillin orally was compared pharmacokinetically with parenteral ampicillin (intravenously and intramuscularly). A cross-over study on healthy volunteers showed that ampicillin concentrations after equimolar doses of bacampicillin orally and ampicillin intramuscularly were of the same order. The mean of the individual peak values (regardless of time of occurrence) after a dose of 800 mg of bacampicillin was 13.1 ± 3.8 μg/ml. Absorption rates of the two doses were similar, as were their distribution volumes (approximately 25% of the body weight). Bioavailability was 87% for bacampicillin, compared to 71% for ampicillin.